A suggestion for evolution of Canada's health regulatory system - Jessica White; Gregor Reid (Canadian Science Publishing, 2018)
Aspects of Canada's health regulatory system are currently being reviewed. This is timely, as the regulation and definition of drugs, foods, and natural health products (NHPs) is in need of revision to facilitate greater transparency and less ambiguity. A number of studies have illustrated the importance of a nutritious diet to prevent and manage chronic disease. Therefore, legislation surrounding food health claims needs to be adjusted so that it is more informative for disease prevention and, in some cases, treatment. Canada is modernizing the regulation of self-care products, under which NHPs, including probiotic products, are listed. With the growing appreciation for the role that microbes play in human health and the recognition that many foods, including those containing probiotic organisms, can prevent or mitigate disease, this provides an opportunity to reassess regulatory categories.